SECURE DICOM IMAGE COMMUNICATION: ADVANCES AND CHALLENGES - Verma, Saurabh; Bhatele, Mukta; Waoo, Akhilesh A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The envisioned system addresses the multifaceted challenges in DICOM image communication by implementing sophisticated digital watermarking algorithms that are resilient against advanced deep learning attacks, ensuring data integrity and bolstering security in healthcare imaging systems. By harmonizing the balance between data protection and patient privacy within legal frameworks, and using privacy-preserving methods, the system adheres to compliance regulations while maintaining patient confidentiality. It also introduces efficient real-time processing algorithms that minimize delays in diagnostic workflows, alongside scalable data management solutions to handle the burgeoning volume of medical data without compromising performance. Further, the system integrates seamlessly with AI algorithms to enhance diagnostic accuracy and efficiency, fostering a synergistic relationship that amplifies the benefits of both digital watermarking and artificial intelligence in medical imaging. This comprehensive approach not only enhances security, privacy, efficiency, scalability, and compatibility but also propels advancements in diagnostic capabilities, significantly improving the effectiveness of healthcare imaging systems.